Congestion-Free Transient Plane (CFTP) Using Bandwidth Sharing During Link Failures in SDN. (5th December 2019) - Vanamoorthy, Muthumanikandan; Chinnaiah, Valliyammai
Abstract: Software-defined networking (SDN) is an emerging trend where the control plane and the data plane are separated from each other, culminating in effective bandwidth utilization. This separation also allows multi-vendor interoperability. Link failure is a major problem in networking and must be detected as soon as possible because when a link fails the path becomes congested and packet loss occurs, delaying the delivery of packets to the destination. Backup paths must be configured immediately when a failure is detected in the network to speed up packet delivery, avoid congestion and packet loss and provide faster convergence. Various SDN segment protection algorithms that efficiently reduce CPU cycles and flow table entries exist, but each has drawbacks. An independent transient plane technique can be used to reduce packet loss but is not as efficient when multiple flows try to share the same link. The proposed work focuses on reducing congestion, providing faster convergence with minimal packet loss and effectively utilizing link bandwidth using bandwidth-sharing techniques. An analysis and related studies show that this method performs better and offers a more reliable network without loss, while simultaneously ensuring the swift delivery of data packets toward the destination without congestion, compared to the other existing schemes.